Implementing the Teaching at the Right Level (TaRL) Approach to Improve Elementary Students' Initial Reading Skills - Muammar, Muammar; Ruqoiyyah, Siti; Ningsih, Nining Surya (Journal of Languages and Language Teaching, 2023)
This research was motivated by students' low initial reading skills in Class I MIN 1 Mataram City. Of the 130 students, 38 students could not read at the initial. This research aims to improve students' initial reading skills by implementing the Teaching at the Right Level (TaRL) Approach Assisted by Inovasi Materials in Class I MIN 1 Mataram City. This type of research is classroom action research (CAR). The research setting is at MIN 1 Mataram City. The study aims to improve students' initial reading skills through the TaRL Approach. The research was carried out in two cycles, which included four stages: planning, implementing and observing, evaluating, and reflecting. The research instruments used were interviews, observations, tests, and documentation. Data analysis was carried out qualitatively and quantitatively. The success of this research is if student activity is at least in the active category and students' initial reading ability is at least 85% of students get a score of 70. The research results show that implementing the Teaching at the Right Level (TaRL) approach assisted by Inovasi Materials can improve students' initial reading ability in Class I MIN 1 City of Mataram. This can be seen from the evaluation results that can be seen from the average value of Cycle I, 66 to 81.36 in Cycle II. Then, the number of students who completed was seen from 20 students in Cycle I to 33 students in Cycle II, or it could be interpreted that the percentage in Cycle I was 52.63%, increasing to 86.84% in Cycle II.